Effect of blend composition and related morphology on the quasi-static fracture performance of LLDPE/PP blends - Rosales, Caren Soledad (2020)
In the present work, the effect of composition and related morphology on the fracture behavior of LLDPE/PP blends was thoroughly investigated. Fracture behaviors evaluated under quasi-static loading conditions and different fracture mechanics methodologies were applied to assess fracture toughness depending on the materials behavior. For pure PP and 2575 blend, J at instability was chosen whereas for blends which exhibited completely ductile behavior (such as LLDPE, 7525 and 5050), the EWF methodology was used. Fracture mechanisms were elucidated with the aid of scanning electron microscopy, and results correlated with blends morphology. It was observed that fracture properties are mostly dominated by the majority component properties. In addition, for the 5050 blend, the presence of a co-continuous morphology is responsible for the high scatter of experimental data obtained.